Short communication: The crustaceans fauna from Natuna Islands (Indonesia) using three different sampling methods - Rianta Pratiwi; DEWI ELFIDASARI (Society for Indonesian Biodiversity, 2020)
Abstract. Pratiwi R, Elfidasari D. 2020. Short communication: The crustaceans fauna from Natuna Islands (Indonesia) using three different sampling methods. Biodiversitas 21: 1215-1226. Research on crustacean fauna has been carried out in Natuna waters. Natuna is the outer islands of Indonesia which is still very abundant in fisheries resources including crustaceans. Unfortunately, research on crustaceans is rarely carried out there, especially on the islands around Natuna. Therefore research and information about fisheries, especially crustaceans are needed. The study was conducted on 12-29 April 2011 and sampling locations around the Bunguran Islands, Sedanu, Kognang, Batang, and Sebangmawang. The sampling collection was focused on three different sampling methods, namely: bottom trawling, transects, and free collection. The purpose of this study is to find out which method is best used in crustacean fauna research and it is expected that the crustacean data obtained can add information about crustacean fauna found in the Natuna Islands. Crustacean fauna, which were collected, showed that species from basic trawlers numbered 66 species, 41 species were from transects and 101 species was from free collections. The total number of individuals from the bottom trawl were 746, from the transect were 65 and from the free collection were 704. From the results of the study using three different methods have advantages and disadvantages of each method. The best method used is the free collection method and bottom trawling, because it can collect many crustacean species.